2015
DOI: 10.1007/s00204-015-1589-3
|View full text |Cite
|
Sign up to set email alerts
|

Common and distinct mechanisms of induced pulmonary fibrosis by particulate and soluble chemical fibrogenic agents

Abstract: Pulmonary fibrosis results from the excessive deposition of collagen fibers and scarring in the lungs with or without an identifiable cause. The mechanism(s) underlying lung fibrosis development is poorly understood, and effective treatment is lacking. Here we compared mouse lung fibrosis induced by pulmonary exposure to prototypical particulate (crystalline silica) or soluble chemical (bleomycin or paraquat) fibrogenic agents to identify the underlying mechanisms. Young male C57BL/6J mice were given silica (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 45 publications
(61 reference statements)
2
32
0
Order By: Relevance
“…Moreover, TIMP1 is secreted into the plasma in certain fibrosing diseases and cancers and, therefore, affects distant tissues in a manner analogous to an endocrine factor. Consistent with this notion, TIMP1 is highly induced during fibrosis in a number of animal models, such as bleomycin- and paraquat-induced lung fibrosis, and fibrosing diseases in humans, such as IPF and liver cirrhosis, implicating dysregulation of TIMP1 expression in the development of fibrosis (Dong et al, 2016; Hayashi et al, 1996; Madtes et al, 2001; Manoury et al, 2006; Selman et al, 2000; Tomita et al, 2007). Nonetheless, the function of TIMP1 in fibrosis, in particular, in the development of lung fibrosis remains largely unclear.…”
Section: Introductionmentioning
confidence: 84%
“…Moreover, TIMP1 is secreted into the plasma in certain fibrosing diseases and cancers and, therefore, affects distant tissues in a manner analogous to an endocrine factor. Consistent with this notion, TIMP1 is highly induced during fibrosis in a number of animal models, such as bleomycin- and paraquat-induced lung fibrosis, and fibrosing diseases in humans, such as IPF and liver cirrhosis, implicating dysregulation of TIMP1 expression in the development of fibrosis (Dong et al, 2016; Hayashi et al, 1996; Madtes et al, 2001; Manoury et al, 2006; Selman et al, 2000; Tomita et al, 2007). Nonetheless, the function of TIMP1 in fibrosis, in particular, in the development of lung fibrosis remains largely unclear.…”
Section: Introductionmentioning
confidence: 84%
“…The lung fibrotic response to CNT exposure resembles the pulmonary response to deposition of fibrogenic foreign bodies in the lungs. In particular, the pathologic features and dynamics of the pulmonary interstitial fibrosis induced by CNTs display a high similarity to those of pneumoconiosis and IPF, both of which are progressive, incurable, and poorly understood human fibrotic lung diseases [24, 28].
Fig.
…”
Section: Carbon Nanotube-induced Lung Fibrosismentioning
confidence: 99%
“…It is known that both MWCNTs and SWCNTs stimulate the production of ROS in vitro and in the lungs [95, 96, 101, 125], which would induce the activation of TGF-β1 in a manner analogous to that of asbestos [126, 127]. In recent studies, we have shown that the lung expression of TSP-1 was significantly induced by MWCNTs in vivo [101], whereas that of MMP-2 was induced during lung fibrosis from exposure to silica, paraquat, or bleomycin [28]. Direct evidence supporting a role of these mediators in the activation of latent TGF-β1 in CNT-induced lung fibrosis awaits further investigation.…”
Section: Tgf-β1mentioning
confidence: 99%
See 1 more Smart Citation
“…The lung lesions elicited by CNT, either multi-walled (MWCNT) or single-walled (SWCNT), resemble the pulmonary response to deposition of foreign bodies such as insoluble dusts (i.e., silica, asbestos, and coal dust) and large biologic masses (i.e., inhaled allergens and microbes, and invading parasites), all of which are capable of inducing lung fibrosis (Dong and Ma 2015a; Dong et al 2015a, b; Husain and Kumar 2005; Morgan and Seaton 1995). The response initiates with a prominent acute inflammation, indicated by recruitment and accumulation of inflammatory cells and elevated secretion of cytokines and growth factors.…”
Section: Introductionmentioning
confidence: 99%